2021
DOI: 10.1016/j.ctro.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

CDK 4/6 inhibitors combined with radiotherapy: A review of literature

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…The risk of neutropenia does not appear to be different than with CDK inhibitors alone [72] , and a small retrospective study showed combination treatment to be safe [73] . Alternatively, other studies have raised concern for pulmonary, GI, and skin toxicities [74] , [75] , [76] , [77] . Due to the dosing schedule of palbociclib, RT can be delivered during the week when patients are not receiving the drug.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of neutropenia does not appear to be different than with CDK inhibitors alone [72] , and a small retrospective study showed combination treatment to be safe [73] . Alternatively, other studies have raised concern for pulmonary, GI, and skin toxicities [74] , [75] , [76] , [77] . Due to the dosing schedule of palbociclib, RT can be delivered during the week when patients are not receiving the drug.…”
Section: Resultsmentioning
confidence: 99%
“…However, the clinical effects of combining palbociclib and RT is least well-known. Several small retrospective studies have reported that the combination of RT and CDK inhibitor was generally well tolerated [ 67 ]. The series mainly reported the follow-up of patients irradiated on metastatic lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, our results suggest that CDK4/6 inhibition + RT is a promising strategy to decrease recurrence and increase local disease control across ER+ and TNBC and that RB may be a potential biomarker for efficacy. Concerns about the safety of concurrent CDK4/6 inhibition and RT remain, and to date, small studies exploring outcomes in patients with MBC receiving palliative radiation and CDK4/6 inhibitor therapy have conflicting results regarding toxicity, depending on the dose/fractionation of radiation and the regions targeted in the metastatic setting (visceral organs) (61)(62)(63)(64). Reassuringly, no studies to date have demonstrated more pronounced side effects of CDK4/6 inhibitors, such as cytopenias and skin desquamation, in women receiving concurrent therapy to the breast or axillary regions.…”
Section: Discussionmentioning
confidence: 99%